Преобразование токового интегрального уравнения магнитного поля электромагнитного перемешивателя - Евдокимов, В.Ф.; Кучаев, А.А.; Петрушенко, Е.И.; Кучаев, В.А. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
System of the scalar integral equations is received for the first symmetric component of rotating magnetic field of the electromagnetic stirrer. In the
system is taken into account symmetries of the magnetic field of the first symmetric component for coordinate planes. The definitional domain of the system there is one eighth part to ferromagnetic core surface lying in the first octant. The order of the
matrixes approximating integral operators in equations is greatly below order of the matrixes approximating integral operators in initial system of the equations.